2010
DOI: 10.1074/jbc.m109.065995
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoxia-controlled FBXL14 Ubiquitin Ligase Targets SNAIL1 for Proteasome Degradation

Abstract: The transcription factor SNAIL1 is a master regulator of epithelial to mesenchymal transition. SNAIL1 is a very unstable protein, and its levels are regulated by the E3 ubiquitin ligase ␤-TrCP1 that interacts with SNAIL1 upon its phosphorylation by GSK-3␤. Here we show that SNAIL1 polyubiquitylation and degradation may occur in conditions precluding SNAIL1 phosphorylation by GSK-3␤, suggesting that additional E3 ligases participate in the control of SNAIL1 protein stability. In particular, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(178 citation statements)
references
References 29 publications
5
167
1
Order By: Relevance
“…This degradation of Snail1 by GSK-3b can be attenuated by Loxl2, a member of the lysyl oxidase gene family (Peinado et al, 2005), resulting in Snail1 stabilization and promotion of EMT. Recently, the hypoxia-controlled Fbxl-14 ubiquitin ligase has been shown to modulate Snail1 protein stability independently of its previous phosphorylation (Vinas-Castells et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This degradation of Snail1 by GSK-3b can be attenuated by Loxl2, a member of the lysyl oxidase gene family (Peinado et al, 2005), resulting in Snail1 stabilization and promotion of EMT. Recently, the hypoxia-controlled Fbxl-14 ubiquitin ligase has been shown to modulate Snail1 protein stability independently of its previous phosphorylation (Vinas-Castells et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Considering previous findings, we can speculate that phosphorylation of residues in different motif fulfill diverse functions to EMT transcriptional factors, which may due to their structure difference. Besides, ubiquitination of EMT transcriptional factors usually result in ubiquitin-dependent degradation, a pathway that was crucial for metastasis repression [33,44,47]. Overall, the molecular mechanism that Snail, Twist and ZEB could be dual-regulated by PTMs broaden our knowledge about function of EMT transcriptional factors during cancer metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reports that the expression of Fbxl14 is markedly downregulated concomitantly with increased levels of its target Snail1 protein during hypoxia, which has been associated with tumor progression [7]. Mkp3, a novel target of Fbxl14 in this study, is involved in the development of cancer and has been suggested as a candidate tumor suppressor protein [9].…”
Section: Dear Editormentioning
confidence: 97%
“…Although approximately 70 FBPs have been identified in humans [4,5], only a few of them have been well characterized. Fbxl14 (F-box and leucine-rich repeat protein 14) has been reported to regulate Snail2 protein during neural crest development of Xenopus laevis embryos [6] and to control Snail1 protein stability in mammalian cells [7]. There are two homologs of Fbxl14 in zebrafish, namely Fbxl14a and Fbxl14b.…”
Section: Dear Editormentioning
confidence: 99%